Dampak Dukungan Sosial Teman Sebaya terhadap Tingkat Self-Esteem Siswa MTs Madrasatul Qur’an - Abdul Lathif; Sholihul Anshori (AS-SABIQUN, 2026)
Quantitative studies that specifically examine the effect of peer social support on self-esteem in the context of madrasahs within tahfidz Islamic boarding school environments remain limited, even though students are required to have high mental resilience and live far from their parents. This study aims to test and analyze the effect of peer social support on the self-esteem level of students at MTs Madrasatul Qur’an Tebuireng Jombang. This study used a causal-associative quantitative approach involving 90 male students selected from a population of 736 students through proportional stratified random sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, then analyzed through classical assumption tests and simple linear regression with the assistance of SPSS version 21. The results showed that peer social support had a positive and significant effect on students’ self-esteem levels (p = 0.000 < 0.05), with an effect contribution of 28.8% (R² = 0.288). The conclusion of this study affirms that the higher the peer social support in the dormitory environment, the higher the level of self-esteem possessed by students. The implications of this study contribute to the development of the Islamic educational psychology literature, particularly regarding the role of ukhuwah Islamiyah in building the psychological well-being of santri, and provide practical input for guidance and counseling teachers in developing peer-group counseling programs in Islamic boarding school environments.